The Digital Playbook A Practitioner's Guide to Smart, Connected Products and Solutions with AIoT - Slama, Dirk; Rückert, Tanja; Thrun, Sebastian; Homann, Ulrich; Lasi, Heiner (Springer Nature, 2023)
This open access book is a practitioner's guide to smart, connected products and solutions. As a hands-on playbook, it combines the business and technical execution perspectives to help product companies, OEMs, manufacturers and equipment operators utilize the full potential of digital enablers, especially Artificial Intelligence (AI), Internet of Things (IoT) and Digital Twins. The Digital Playbook provides comprehensive and actionable guidance, helping to address the challenges of creating sustainable and scalable digital business models, managing cocreation and sourcing, setting up the digital organization, and handling the legal aspects. For the technical execution perspective, the playbook includes the AIoT Framework, which explains how to combine data science and AI engineering with Digital Twins, as well as software development for cloud and edge. The integration with physical product development and retrofit integration of existing equipment is included as well. A pragmatic, agile approach is introduced that takes common agile inhibitors into consideration. A holistic AIoT DevOps approach is described, which combines key elements of DevOps for cloud, edge and AI. Enterprise readiness is ensured by looking at trust and security as well as reliability and resilience for AIoT. A large number of real-world examples and case studies help ensure practical relevance. Readers should have a previous, general understanding of digital strategies and technologies. This book offers readers a clear understanding of the opportunities, as well as the challenges related to building and operating smart, connected products and solutions. They are given a set of tools and blueprints, which they can apply to their practical work in this space. ;